Increasing periods after seeding under twice‐annually harvested alfalfa reduces soil carbon and nitrogen stocks in a semiarid environment. (13th July 2020) - Wang, Wei; Cheng, Zheng‐Guo; Li, Meng‐Ying; Wang, Bao‐Zhong; Li, Ji‐Yuan; Wang, Wei; Su, Yong‐Zhong; Batool, Asfa; Xiong, You‐Cai
Abstract: It is unclear how multi‐year planting of alfalfa affects soil carbon and nitrogen stocks. We investigated alfalfa fields which had been seeded at the start of the first year and then harvested twice a year for 2, 5, 8, 10 and 20 years (wheat field, CK) in the semiarid Loess Plateau. In general, soil water storage tended to drop from the second to eighth year and then tended to increase in the tenth and twentieth years, displaying a V‐shaped curve. Compared with CK, soil organic carbon (SOC) under alfalfa was significantly improved at the second year. It started to decrease to the lowest level at the eighth year, and then recovered to increasing at the tenth and twentieth years. Interestingly, soil C/N ratio, microbial biomass carbon, easily oxidizable organic carbon, and high fraction organic carbon followed a similar trend as SOC did, falling to lows in the eighth year, that is, 8.28 and 18.1 mg kg −1 and 1.91 and 10.2 g kg −1, respectively. Notably, light fraction organic carbon and particulate organic carbon increased up to their highest values in the eighth year (1.78 and 2.81 g kg −1 ). Moreover, soil NH4 + ‐N, NO3 − ‐N, and microbial biomass nitrogen fell, following a similar dynamic as SOC. It can be argued that soil C and N sequestration be were weakened in successive planting years due to enhanced mineralization rates of C and N pools. The possible mechanism causing such phenomenon is also discussed. Multi‐year planting of alfalfa reduced the soil C and N stocks; therefore, alfalfa fields should be replanted in successive years only for an optimum number of years of planting.